2023
DOI: 10.1038/s41398-023-02556-6
|View full text |Cite
|
Sign up to set email alerts
|

Early-life differences in the gut microbiota composition and functionality of infants at elevated likelihood of developing autism spectrum disorder

Abstract: Evidence from cross-sectional human studies, and preliminary microbial-based intervention studies, have implicated the microbiota-gut-brain axis in the neurobiology of autism spectrum disorder (ASD). Using a prospective longitudinal study design, we investigated the developmental profile of the fecal microbiota and metabolome in infants with (n = 16) and without (n = 19) a family history of ASD across the first 36 months of life. In addition, the general developmental levels of infants were evaluated using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 84 publications
0
8
1
Order By: Relevance
“…Fifth and finally, we used the Gesell, PEP-3, and CARS scales to measure developmental abilities, and ASD symptoms, respectively. In future studies, it will be recommended to use ADOS-2 ( 62 ) or ADI-R ( 63 ) for describing the core symptoms of ASD, and use the Griffiths ( 64 ) or Mullen Scales of Early Learning (MSEL) ( 65 ) for evaluating developmental abilities.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth and finally, we used the Gesell, PEP-3, and CARS scales to measure developmental abilities, and ASD symptoms, respectively. In future studies, it will be recommended to use ADOS-2 ( 62 ) or ADI-R ( 63 ) for describing the core symptoms of ASD, and use the Griffiths ( 64 ) or Mullen Scales of Early Learning (MSEL) ( 65 ) for evaluating developmental abilities.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of certain microorganisms has been linked to enduring effects on neurogenesis, synaptogenesis, axonal and dendritic growth, and the establishment of neural connections, all of which can influence the development of ASD ( Rogers et al., 2016 ). Research indicates that infants at higher risk of ASD suffer different gut microbiota composition during a crucial developmental period for the gut microbiota and brain ( Zuffa et al., 2023 ). This indicates that alterations in gut microbiota during early development may have persistent impacts on the formation of neuronal pathways.…”
Section: Discussionmentioning
confidence: 99%
“…↑ Acinetobacter spp. ↑GABA degradation 98 Epilepsy ↓ Anaerotruncus ↓ Peptococcaceae ↓ Prevotellaceae Ga6A1 group ↓ Ruminococcus torques group ↓ Peptococcus y Ruminococcus gauvreauii group ↓ Pseudomonas graminis* ↓ Ruminococcaceae bacterium AM2 ↓GABA levels 102 ↓ Akkermansia muciniphila ↓ Parabacteroides ↓GABA/glutamate levels 105 Autism spectrum disorder ↑ Clostridium* ↑ Klebsiella ↓ Bifidobacterium* ↓ Prevotella copri ↓ Feacalibacterium prausnitzii ↓ Haemophilus parainfluenzae ↓GABA levels 108 , 109 ↑ Escherichia/Shigella* ↑ Lachnoclostridium ↑ Megamonas ↑ Megasphaera* ↑ Veillonella* ↓ Bacteroides ↓ Akkermansia ↓ Parabacteroide ↓ Rothia ↑GABA/glutamate levels 110 ↑ Dialister ↑ Escherichia/Shigella ↑ Bifidobacterium* ↓ Prevotella 9 ↑GABA precursor levels 111 Attention deficit hyperactivity disorder ↑ Bacteroides ↑ Dorea ↑ Erysipelotrichaceae ↑ Ruminococcaceae ↑ Dialister ↓ Lachnospiraceae ↓ Ruminococcus ↓ Bacteroides ↓ Lachnospiraceae ↓ Enterococcus ↓GABA levels (putative) 114 ↑ Bifidobacterium adolescentis ↑ Bifidobacterium animalis ↑ Bifidobacterium breve ↑ Bifidobacterium longum ↑ Bacteroides ovatus ↑ Bacteroides uniformis ↑ Fusobacterium ulcerans ↑ Enterocococcus avium ↑ Enterococcus gallinarumi ↓ Faecalibacterium prausnitzii ↑GABA levels (putative) …”
Section: Gaba As a Mediator Of The Gut–brain Axismentioning
confidence: 99%
“…Specifically, 76–87% of beta2-toxin-producing Clostridium perfringens were significantly higher in children with ASD compared to control children, indicating that these opportunistic pathogens thrive in immature or compromised immune systems 107 . A recent study has shown that infants with increased-likelihood of ASD have a decreased abundance of Bifidobacterium but an increased abundance of Clostridium and Klebsiella compared to those with lower likelihood of ASD 108 . Moreover, fecal GABA levels of infants with increased likelihood of ASD were lower than those with lower likelihood of ASD, in which fecal GABA levels are positively correlated with Bifidobacterium , but negatively correlated with Clostridium 108 .…”
Section: Gaba As a Mediator Of The Gut–brain Axismentioning
confidence: 99%
See 1 more Smart Citation